(untitled) (Fiep Bulletin - online, 2012)
This paper has reviewed the literature in order to reflect on the role of physical education in public policies for health promotion. It was found that the epidemiological data highlight the need for preventive and palliative up in the field of population health. It was concluded that the role of physical education in public policy for health promotion would be to work early on in schools, families, workplaces and wherever a social group is established, the articulation of its fundamental assumptions in order to create, maintain and strengthen the habit of regular physical activity, independently or not being restricted by the dependence of the political will of some individuals in society.